Carbon footprint assessment and reduction strategies for aquaculture: A review - Haocheng Li; Xiaoqing Zhou; Li Gao; Jian Liang; Huiru Liu; Yongren Li; Limei Chen; Yongjun Guo; Shuang Liang (Journal of the World Aquaculture Society)
Abstract Aquaculture generates less greenhouse gas emissions compared to other agriculture practices due to its limited land‐use changes, improved feed conversion rates, and reduced methane emissions from animals' digestive systems. The aquaculture carbon emissions come from various production stages, including feed production, farm operations, processing, transportation, and so forth. This review illustrates the theories, calculation methods, and practical applications of the carbon footprint in fisheries and aquaculture, as well as the challenges and strategies for emission reduction. The factors influencing the carbon footprint of fishing and manufacturing aquaculture are also discussed. Further research should focus on refining carbon footprint assessment techniques, promoting green technologies and sustainable aquaculture practices. Managing aquaculture's carbon footprint though is crucial for mitigating environmental impacts and supporting sustainable development.